2020
DOI: 10.21203/rs.3.rs-48063/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor-Mutant Non-Small Cell Lung Cancer and Choroidal Metastases: Long-Term Outcome and Response to Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors

Abstract: Background: Although previously reported, little is known about choroidal metastasis in EGFR-mutant NSCLC. Methods: In this single-center retrospective cohort including 83 consecutive metastatic EGFR-mutant NSCLC patients, from Sept. 2015 to Oct. 2018, six exhibited symptomatic choroidal metastases. All brain MRI scans performed in the EGFR-mutant patients were reviewed, with one case of asymptomatic choroidal metastasis identified. Kaplan-Meier analysis and log-rank test were conducted to assess median overal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…They reported complete resolution within 3 months and maintenance for 17 months. In many cases, osimertinib has been associated with a reduction in choroidal lesions and improvement in symptoms such as visual disturbances, brain metastases, and metastatic disease [4,[7][8][9]. The reported side effects were within the control limits [8].…”
Section: Discussion/conclusionmentioning
confidence: 96%
See 3 more Smart Citations
“…They reported complete resolution within 3 months and maintenance for 17 months. In many cases, osimertinib has been associated with a reduction in choroidal lesions and improvement in symptoms such as visual disturbances, brain metastases, and metastatic disease [4,[7][8][9]. The reported side effects were within the control limits [8].…”
Section: Discussion/conclusionmentioning
confidence: 96%
“…The case reports on the efficacy of osimertinib in metastatic choroidal tumors of primary NSCLC are summarized in Table 1. Previously, osimertinib was often reported as a second-line therapy [4,7,8,11], but since the FLAURA trial, osimertinib has been used as a first-line therapy. However, few reports have demonstrated the efficacy of osimertinib as a first-line therapy for metastatic choroidal tumors [9,10].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyrosine kinase receptors of the ERBB family include four members: HER-1/ERBB1/EGFR, HER-2/ ERBB2, HER-3/ ERBB3, and HER-4/ ERBB4 [18,19]. The former researches indicated that the ERBB receptor family is closely associated with cell proliferation and oncogenic events [20].…”
Section: Introductionmentioning
confidence: 99%